The dual function of microglial polarization and its treatment targets in ischemic stroke - Mo, Yong; Xu, Weilin; Fu, Kaijing; Chen, Hainan; Wen, Jing; Huang, Qianrong; Guo, Fangzhou; Mo, Ligen; Yan, Jun (Frontiers in Neurology, 2022)
Stroke is the leading cause of disability and death worldwide, and ischemic stroke occurs in about 5‰ of the global population every year. In recent years, there have been many studies on the inflammatory response after stroke. Microglia/macrophage polarization has a dual function and is critical to the pathology of ischemic stroke. Microglia activation is important for reducing neuronal apoptosis, enhancing neurogenesis and promoting functional recovery after cerebral ischemia. In this review, we review the physiological characteristics and functions of microglia in the brain, activation and phenotypic polarization of microglia and macrophages after stroke, signaling mechanisms of polarization states, and microglia for contributions to brain pathology and repair. We summarize recent advances in stroke-related microglia research, focusing on breakthroughs in therapeutic strategies for microglia/macrophage responses after stroke, thereby providing new ideas for the treatment of ischemic stroke.